What Drives China's Interbank Market? - Porter, Nathan (IMF Working Papers; Working Paper ;, 2009)
Interest rates in China comprise a mix of both market determined interest rates (interbank rates and bond yields), and regulated interest rates (lending and deposit rates), reflecting China's gradual process of interest rate liberalization. We argue, using a theoretical model and empirical analysis, that the regulation of key retail interest rates diminishes the ability of the market determined rates to act as independent price signals, or as benchmarks for use in asset pricing and monetary policy. Further interest rate liberalization should, therefore, strengthen the information conveyed by movements in interest rates, allowing for the better pricing of risk and capital.